Levels of MMP-9 in patients with intracranial aneurysm: Relation with risk factors, size and clinical presentation - Rojas, Hugo Alberto; Fernandes, Karla Simone da Silva; Ottone, Mariana Rodrigues; Magalhães, Kênia Cristina S. Fonseca de; Albuquerque, Lucas Alverne Freitas de; Pereira, Julio Leonardo Barbosa; Vieira-Júnior, Gerival; Sousa-Filho, José Lopes; Costa, Bruno Silva; Sandrim, Valéria Cristina [UNESP]; Dellaretti, Marcos; Simões, Renata Toscano (Elsevier, 2018)
Background: Intracranial aneurysms are arterial anomalies affecting 2% to 3% of the general population in the world and these ruptures are associated with a high mortality. Some risk factors, such as age, gender, smoking, alcohol, hypertension and familial history are associated with the number of aneurysms and their size. In addition, inflammatory processes within the blood vessels of the brain can activate matrix metalloproteinase-9 (MMP-9), which degrades various components of the extracellular matrix, such as elastin. Thereby, this work has aimed at evaluating the relationship between plasma MMP-9 levels and the risk factors that are associated with intracranial aneurysm, as well as investigating the aneurysm statuses (ruptured and unruptured) and comparing them with the control volunteers. Methods: Between August 2014 to June 2016, blood samples were collected from 282 patients (204 ruptured and 78 unruptured saccular intracranial aneurysms) and 286 control volunteers. The MMP-9 plasma levels were measured by ELISA. Statistical analyzes were performed with SPSS software when using parametric or nonparametric tests, after the normality tests. Results: Higher levels of MMP-9 were found in the aneurysm groups as a whole and when they were stratified by rupture status, then compared with the control group (p < 0.0001). When stratifying them by diameter, those smaller than 7 mm presented high levels of MMP-9 (p < 0.0001), especially in the ruptured ones. As for risk factors, hypertension and smoking were the most important. However, hypertension was mostly associated with the ruptured aneurysms (p < 0.0001). Conclusions: High levels of MMP-9 were found in smaller ruptured and unruptured intracranial aneurysms (<7 mm) with strongest statistical associations than other sizes, especially when associated with smoking and hypertension.
Keywords: Gelatinase-B; Intracranial aneurysm; Metalloproteinase-9; Subarachnoid hemorrhage